A method for deducing pressure–sinkage of tracked vehicle in rough terrain considering moisture and sinkage speed. (October 2018) - Yang, Congbin; Yang, Guang; Liu, Zhifeng; Chen, Huaxiong; Zhao, Yongsheng
Highlights: The relationships of major factors with the deformation of soil were discussed. A new method deducing pressure–sinkage of tracked vehicle were proposed. Water content and repeated loading are considered in the method. The prediction results showed good agreement with the experimental results. Abstract: Tracked vehicles assume an important role in engineering and agriculture. Supporting-trafficability is the lifeline of tracked vehicles. The terrain characteristics is concerned with the relationships critical in defining the mobility of tracked vehicles. Conventional terramechanics models cannot accurately describe the relationship between tracks and soil. A major problem is that these models do not account for the water content in the soil and sinkage speed. Water content is an important factor affecting sinkage of vehicles, which in turn affects vehicles' driving resistance. Increased driving resistance is a barrier to the mobility of an tracked vehicle. Considering sinkage speed is conducive to describe the trafficability of tracked vehicle moving at high speed. In this paper, the terrain characteristics to describe the relationship of the pressure/sinkage of four common soil types in Southwest China were measured using soil bin tests. We discuss characteristics like high sinkage speed, water content variation, and repeated loading, as well as the relationships of these major factors with the deformation of soil. We present a method to deduce the pressure-sinkage relationship for track shoes using the stress-displacement relationship model proposed by Bekker. The described method advances the study and understanding of track-terrain interaction in complex environments.